Community-Based Learning Practices in a Down Syndrome Family (POTADS) Community - Riska Trinanda; Jajat S Ardiwinata; Yanti Shantini; Elih Sudiapermana; Putri Kiki Sushella (Universal Education Jurnal Teaching and Learning, 2026)
This study aims to identify the implementation of Community-Based Learning (CBL) within the POTADS West Java community as a family-based community of children with Down syndrome. The study employed a qualitative descriptive approach with an observational design, based on four direct observations supported by documentation of community activities. The analysis was guided by key CBL indicators, including active participation, contextual and experiential learning, collaboration and equality, problem-solving orientation, and the community as the learning agent. The findings reveal that all CBL indicators were consistently manifested across various community activities. The learning process was participatory, grounded in real-life experiences, and involved collaborative interactions among children, parents, volunteers, and professionals. In addition, the activities were oriented toward addressing real challenges faced by community members and were collectively managed by the community itself. These findings confirm that CBL is not merely a theoretical construct but is empirically implemented within disability-oriented communities. Furthermore, the study highlights the central role of family involvement in strengthening the implementation of CBL within community contexts. Thus, the POTADS West Java community represents a concrete example of inclusive, contextual, and sustainable community-based learning. This study contributes to the understanding of CBL implementation in family-based community settings and emphasizes the importance of integrating family roles in the development of adaptive and inclusive non-formal education.